Evaluation of nitric oxide synthase levels in women with hypertensive disorders during pregnancy - Sіusіuka, V. H.; Belenichev, I.; Kyrychenko, M.; Сюсюка, Володимир Григорович; Бєленічев, Ігор Федорович; Кириченко, Михайло Михайлович (My University, 2024)
Preeclampsia (PE) is a polyetiological hypertensive disorder (HD) that develops in women after the 20th week of pregnancy. It is characterized by elevated blood pressure and proteinuria. This condition adversely affects the health of both the mother and the fetus and can lead to various complications. Despite numerous studies, the pathogenesis of PE remains poorly understood. However, there is compelling evidence that endothelial dysfunction (ED) and endotheliosis (ES) play significant roles in its development. ED impairs the vessels’ ability to relax, while ES damages the structure of the endothelium. Both conditions are interrelated in the pathogenesis of PE. Nitric oxide (NO) is a crucial factor in the regulation of vascular tone, and its synthesis is controlled by the enzyme called endothelial NO-synthase (eNOS). In the context of PE, decreased enzyme activity can lead to reduced NO synthesis. This, in turn, impairs the relaxation of the vascular wall and contributes to the development of ED. Although the role of eNOS in the pathogenesis of PE is currently under debate, measuring its concentration could be clinically relevant for women with HD. The aim of the research. To evaluate the level of endothelial NO-synthase in women with hypertensive disorders during pregnancy. Materials and methods. Sixty-five women in the 3rd trimester of pregnancy, who were registered in the Advisory and Diagnostic Department of the Communal Non-profit Enterprise «Regional Perinatal Center» of the Zaporizhzhia Regional Council, participated in the study. The main group consisted of 35 women with singleton pregnancies, the course of which was complicated by gestational hypertension without significant proteinuria (GH), moderate or severe preeclampsia (PE). The control group consisted of 30 women with singleton pregnancies, the course of which was uncomplicated and concluded with physiological delivery. All pregnant women had their serum eNOS concentration measured by enzyme-linked immunosorbent assay (ELISA). Research results. According to the study results, the average eNOS concentration in the main group was 414.44±20.06 pg/ml (σ = 118.69), while in the control group it was 1347.21±72.05 pg/ml (σ = 394.61). This difference is statistically significant (p < 0.001). Correlation analysis revealed an inverse relationship between the eNOS level and the severity of PE (ρ = -0.581, p < 0.001). Conclusions. The level of eNOS in the peripheral blood serum of women whose pregnancy was complicated by hypertensive disorders was significantly lower compared to that in pregnant women without hypertensive disorders (p < 0.001). The average eNOS concentration in pregnant women with clinical manifestations of hypertensive disorders was 414.44±20.06 pg/ml. This was more than three times lower than the corresponding level in pregnant women without clinical manifestations, which was 1347.21±72.05 pg/ml. According to the results of the correlation analysis, an inverse relationship was established between the level of eNOS and the severity of hypertensive disorders (ρ = -0.581, p < 0.001). Прееклампсія (ПЕ) – це поліетіологічний гіпертензивний розлад (ГР), який розвивається у жінок після 20-го тижня вагітності і проявляється підвищенням артеріального тиску та протеїнурію. Цей стан негативно впливає на стан здоров’я матері і плода та може призводити до розвитку різноманітних ускладнень. Незважаючи на велику кількість фундаментальних досліджень, патогенез розвитку ПЕ на сьогоднішній день залишається остаточно не з’ясованим, але існують надійні свідчення, що ендотеліальна дисфункція (ЕД) та ендотеліоз (ЕЗ) відіграють важливу роль у ньому. Процеси ЕД знижують здатність судин до релаксації, а ЕЗ пошкоджує структуру ендотелію. Обидва ці стани взаємодіють у патогенезі ПЕ. Оксид азоту (NO) є важливим фактором у регуляції судинного тонусу, а його синтез контролюється ферментом ендотеліальна NO-синтаза (eNOS). У контексті патогенезу ПЕ зниження активності ферменту може призвести до зменшення синтезу NO, що, у свою чергу викликає порушення релаксації судинної стінки та веде до розвитку ЕД. Хоча на сьогодні існує дискусія про роль eNOS у патогенезі ПЕ, визначення його концентрації може бути клінічно доцільним для жінок з ГР. Мета дослідження. Дати оцінку рівня eNOS у жінок з гіпертензивними розладами під час вагітності. Матеріали та методи. У дослідженні взяли участь 65 жінок в ІІІ триместрі вагітності, які знаходились на обліку в консультативно-діагностичному відділенні Комунального некомерційного підприємства «Обласний перинатальний центр» Запорізької обласної ради. Основна група складалася з 35 жінок, з одноплідною вагітністю, перебіг якої був ускладнений гестаційною гіпертензією без значної протеїнурії (ГГ), помірною або важкою ПЕ. Контрольна група складалася з 30 жінок з одноплідною вагітністю, перебіг якої не було ускладнено, і яка завершилась фізіологічними пологами. Всім вагітним було проведено визначення концентрації eNOS у сироватці крові шляхом ферментного імуноферментного аналіз (ELISA). Результати дослідження. За результатами проведеного дослідження встановлено, що середнє значення концентрації eNOS у основній групі сановило 414.44±20.06 пг/мл (σ = 118.69), а у контрольній групі – 1347.21±72.05 пг/мл (σ = 394.61). Ця відмінність є статистично значимою (p < 0,001). Кореляційний аналіз виявив зворотний зв’язок між рівнем eNOS та ступенем тяжкості ПЕ (ρ = -0.581, p < 0.001). Висновки. Рівень eNOS у сироватці периферичної крові жінок, вагітність яких була ускладнена гіпертензивними розладами був достовірно нижчим у порівнянні з вагітними без гіпертензивних розладів (p < 0,001). Середній показник концентрації eNOS у вагітних з клінічними проявами гіпертензивних розладів становив 414.44±20.06 пг/мл, що було в три рази нижчим за відповідний показник у вагітних без клінічних проявів – 1347.21±72.05 пг/мл. Згідно з результатами кореляційного аналізу між рівнем eNOS та ступенем тяжкості гіпертензивних розладів встановлено зворотний зв’язок (ρ = -0.581, p < 0.001).
Оцінювання рівня ендотеліальної NO-синтази у жінок з гіпертензивними розладами під час вагітності
Сюсюка В. Г. - ORCID: 0000-0002-3183-4556; Бєленічев І. Ф. - ORCID: 0000-0003-1273-5314; Кириченко М. М. - ORCID: 0000-0002-8658-9148.
Keywords: eNOS; endothelial dysfunction; endothelial NO synthase; endotheliosis; gestational hypertension; hypertensive disorders; nitric oxide; NO; pregnancy; preeclampsia; вагітність; гіпертензивні розлади; гестаційна гіпертензія; ендотеліальна дисфункція; ендотеліальна NO-синтаза; ендотеліоз; оксид азоту; прееклампсія